Cigarette smoking, alcohol drinking, and oral cavity and pharyngeal cancer in the Japanese: a population-based cohort study in Japan. Issue 2 (March 2018) - Lu, Yuquan; Sobue, Tomotaka; Kitamura, Tetsuhisa; Matsuse, Ryoichi; Kitamura, Yuri; Matsuo, Keitaro; Ito, Hidemi; Oze, Isao; Shimazu, Taichi; Yamaji, Taiki; Iwasaki, Motoki; Sasazuki, Shizuka; et al.
Abstract : The effects of cigarette smoking and alcohol drinking on the incidence of oral cavity and pharyngeal cancer (OCPC) in the Asian population have been poorly understood. To assess the effects of cigarette smoking, alcohol drinking, and facial flushing response on incidence of OCPC, a total of 95 525 middle-aged and older eligible individuals were followed in a large-scale population-based cohort study in Japan from 1990 to 2010. In this study, the person-years of observation were 698 006 in men and 846 813 in women, and a total of 222 cases (men=160, women=62) of OCPC were newly diagnosed during the study period. A multivariate Cox proportional-hazards model was used to assess the incidence risk of OCPC and subsites by cigarette smoking and alcohol drinking. The result showed that cigarette smoking and regular alcohol drinking were associated significantly with the incidence of OCPC in men. Compared with nonsmokers and nondrinkers, current male smokers showed a hazard ratio (HR) of 2.37 [95% confidence interval (CI)=1.51–3.70] and regular male drinkers showed an HR of 1.82 (95% CI=1.20–2.76). Cigarette smoking also increased the risk of OCPC among male heavy alcohol drinkers (HR=4.05, 95% CI=2.31–7.11). However, there was no significant association between facial flushing response and OCPC. In conclusion, cigarette smoking and alcohol drinking are independent risk factors for OCPC and its subsites in the male Japanese population.